2018
DOI: 10.3389/fpsyg.2018.01943
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Language Experience on Attention to Faces in Infancy: Evidence From Unimodal and Bimodal Bilingual Infants

Abstract: Faces capture and maintain infants’ attention more than other visual stimuli. The present study addresses the impact of early language experience on attention to faces in infancy. It was hypothesized that infants learning two spoken languages (unimodal bilinguals) and hearing infants of Deaf mothers learning British Sign Language and spoken English (bimodal bilinguals) would show enhanced attention to faces compared to monolinguals. The comparison between unimodal and bimodal bilinguals allowed differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 38 publications
4
32
1
Order By: Relevance
“…When this group of 60 infants was considered as a whole, we found activation in response to audiovisual infantdirected spoken language in a wide bilateral network, which included the posterior temporal and the inferior frontal areas. This pattern of activation is similar to the network involved in spoken language processing in adults (Price, 2010) and also to that previously reported in infants (Altvater-Mackensen & Grossmann, 2016;Dehaene-Lambertz et al, 2002, 2010May et al, 2018;Minagawa-Kawai et al, 2010;Pena et al, 2003;Perani et al, 2011;Sato et al, 2012;Shultz et al, 2014;Vannasing et al, 2016). Sign language elicited activation in a few channels located in the right temporoparietal area.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…When this group of 60 infants was considered as a whole, we found activation in response to audiovisual infantdirected spoken language in a wide bilateral network, which included the posterior temporal and the inferior frontal areas. This pattern of activation is similar to the network involved in spoken language processing in adults (Price, 2010) and also to that previously reported in infants (Altvater-Mackensen & Grossmann, 2016;Dehaene-Lambertz et al, 2002, 2010May et al, 2018;Minagawa-Kawai et al, 2010;Pena et al, 2003;Perani et al, 2011;Sato et al, 2012;Shultz et al, 2014;Vannasing et al, 2016). Sign language elicited activation in a few channels located in the right temporoparietal area.…”
Section: Discussionsupporting
confidence: 88%
“…Areas of the frontal and temporal cortex are crucial to language processing in adulthood. These regions are already activated in response to spoken language in the first few days or weeks of life (Altvater-Mackensen & Grossmann, 2016;Dehaene-Lambertz, Dehaene, & Hertz-Pannier, 2002;Dehaene-Lambertz et al, 2006, 2010May, Gervain, Carreiras, & Werker, 2018;Minagawa-Kawai et al, 2010;Pena et al, 2003;Perani et al, 2011;Sato et al, 2012;Shultz, Vouloumanos, Bennett, & Pelphrey, 2014;Vannasing et al, 2016). As in adults, brain responses to speech in infants are often found to be greater in amplitude in the left than in the right hemisphere (Altvater-Mackensen & Grossmann, 2016;Dehaene-Lambertz et al, 2002, 2010Minagawa-Kawai et al, 2010;Pena et al, 2003;Shultz et al, 2014;Vannasing et al, 2016), but this left lateralization is not always observed in infants (Dehaene-Lambertz et al, 2006;May, Byers-Heinlein, Gervain, & Werker, 2011;May et al, 2018;Perani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This criterion was chosen in order to minimize loss of data while also providing sufficient looking data necessary to reflect a clear fixation and systematic scanning, especially in the case of static images which do not hold attention as well as dynamic stimuli. This criterion is similar to other studies utilizing similar types of static stimuli [Elsabbagh et al, ; Mercure et al, ; Oakes & Ellis, ]. Of note, modifying this valid looking criterion to 200 ms and 1000 ms did not impact the results of the study as they are described below.…”
Section: Methodssupporting
confidence: 76%